Oil Prices Shocks and Government Expenditure - Raouf, Engy (International Journal of Energy Economics and Policy, 2021)
This study employs the vector autoregressive model (VAR), impulse response function and variance decomposition to study the impact of oil price shocks on components of government spending on both oil-exporting and oil importing countries over the period from 1980 to 2018. While the vast majority of previous studies focused on the impact of oil price shocks on government spending, this study emphasized the impact of these shocks on the current and capital government expenditure. It was found that oil price shocks affect government current expenditure positively in the two groups of countries. While it affects government capital expenditure positively in oil-exporting countries and negatively in oil-importing countries. Keywords: Oil-exporting countries, Oil-importing countries, Oil price, VAR model, government expenditures. JEL Classifications: H5, O13, Q43 DOI: https://doi.org/10.32479/ijeep.11172